Systematic Literature Review: Inclusive Education's Impact on the Academic Performance of Social and Emotional Barriers. - Maksud Khashimov (Universitas Pendidikan Indonesia (UPI), 2022)
Inclusive education has become an increasingly relevant topic in the context of education. Evaluating inclusive education programs and providing competency training for teachers can be crucial steps in enhancing the performance of inclusive education. This research aims to delve into a comprehensive understanding of the relationship between inclusive education and the socio-emotional development within the educational context. The research employs the Systematic Literature Review (SLR) method to gather and analyze data from 21 relevant articles on the examined topic. The findings indicate that implementing inclusive approaches and specific teaching strategies can positively impact the learning development and academic performance of children with special needs. The importance of ensuring equal opportunities for these children to receive quality education is also highlighted in this article. The research results provide insights into the necessity of inclusive approaches and adequate social support to holistically facilitate the development of socio-emotional skills in children with special needs. The article underscores significant implications for the development of inclusive education for children with special needs, revealing that appropriate inclusive approaches and teaching strategies can aid in improving their learning development and academic performance. These implications reinforce the need for adequate social support and holistic approaches to create an inclusive, supportive, and stimulating educational environment that fosters the positive potential of children with special needs.